O14 Diagnosis and treatment of helicobacter pylori gastritis in east London. Aiming for further integrated care with general practice to improve treatment outcomes. (12th September 2022) - Derrick, Jonathan; McKenna, Jillian; Bryant, Victoria; Lambourne, Jonathan; Naik, Sandhia; Kadir, Ahmed; Deb, Protima; Croft, Nick; Gasparetto, Marco
Abstract : Introduction/Background: Joint ESPGHAN-NASPGHAN guidelines1 for the management of Helicobacter pylori (h. pylori) in children and adolescents were last updated in 2016, in view of the rising prevalence of antibiotic-resistant strains. More recent NICE guidelines2 published in 2021 only focus on adult patients. Aim: We performed an internal audit at our tertiary level unit in East London, an area with ethnic diversity and a high prevalence of H. pylori infection, to benchmark our practice against national and international recommendations. Subjects and Methods: Between January 2015 and December 2017, 40 children had a confirmed diagnosis of H.pylori gastritis based on histological examination of gastric biopsies. Retrospective clinical data were collected independently by 2 reviewers using information from the electronic patient records. Baseline characteristics (age at time of diagnosis, gender, co-morbidities) and relevant details (H. pylori faecal antigen result, symptoms at diagnosis, endoscopic and histological findings, treatments and follow-up) were recorded in an anonymised Excel spreadsheet and evaluated. Results: Within the study period, H. pylori antigen test was undertaken on faecal samples from 702 children in our catchment area, of which 638 (91%) were positive. Forty children (24 males, mean age 11.7 years, median 13 +/- SD 3.94, range 3–16) were referred to our tertiary level centre for a diagnostic confirmation based on histological examination of gastric biopsies. The most common symptom at referral was abdominal pain in 30/40 (75%) patients, with a specific epigastric location in 19 (47.5%). Eighteen (45%) patients presented with nausea, reflux or vomiting, 4 with chest pain and 5 (12.5%) with anaemia (4 of these required pre-endoscopy blood transfusion). Three patients had gastric ulcers and 5 had duodenal ulcers. Rapid urease test (CLO) was positive in 77% of the patients tested (24/31). Gastritis on histology was severe in 21%, moderate in 37%, and mild in 42%. The majority of patients (69%) responded to 1st (amoxicillin/clarithromycin/PPI) or 2nd line (clarithromycin/metronidazole/PPI) treatments. Twenty-six (65%) were re-tested with H. pylori faecal antigen to confirm eradication and this was successfully achieved in 69% of this group. From the records available to us only 30% of the time were family members tested in the community and successfully treated if positive. Conclusions: Significant testing appears to be happening in the community without patients being referred to tertiary services for endoscopy. Patients who do have endoscopy are more likely to have had long standing H. pylori which in our cohort generally responded well to therapy. However, a significant proportion of our cohort was not assessed for eradication and it was difficult to tell if testing of family members had occurred and actioned upon. We suggest that this should be a future emphasis for future guidelines. It also highlights the ongoing requirement for more integrated and joined up care for paediatric services especially between general practice and specialist paediatric care. References: Jones NL, Koletzko S, Goodman K, et al. Joint ESPGHAN/NASPGHAN guidelines for the management of helicobacter pylori in children and adolescents (update 2016). Journal of Pediatric Gastroenterology and Nutrition 2017;64 (6):991–1003. http://pathways.nice.org.uk/pathways/dyspepsia-and-gastro-oesophageal-reflux-disease